Participant Observation in a Case Study on Web Design Process of E-retail Website - Rashid, Rashdan Bin (Information Management and Business Review, 2013)
Studies on developing models for e-retail implementation for consumer co-operative business are very scarce. Co-operative businesses appear to be anxious about going into online retailing since Malaysian Internet shopping is still new, customers are not very familiar and skeptical towards online shopping. Consequently a case study (participant observation) will be undertaken in this study to accomplish main aim in implementation Content Management System (CMS) in developing design process of consumer co-operative website. Web design process model by Kiatruangkrai et al. (2010) and Goi(2007a) have been the foundation guideline in designing the website. Package selection web based application has been used in design stage which can easily help non professional web developer to design their online shopping website. As a conceptual paper, this research is limited to literature and prior research. It offers the benefit to new direction for further research on web design process model. This paper provides researcher with a proposed model of web design process. The proposed model should also be tested in relation with e retail business.